Tanggung Jawab PT. Pos Indonesia Terhadap Konsumen dalam Pengiriman Barang yang Hilang atau Mengalami Kerusakan pada Barang Menurut Undang-Undang Nomor 8 Tahun 1999 di Kota Atambua - Mohamad Farhan Subang; Orpa Juliana Nubatonis; Yossie M. Y. Jacob (Lembaga Pengembangan Kinerja Dosen, 2024)
Public services today are additional needs whose role is very important in society because they can relieve the community and help national development which aims to realize a just and prosperous society in the era of economic democracy. However, public services are indeed loaded with various problems, what's more, the range itself is very wide, covering both the profit and non-profit sectors. One of the means of shipping goods that can be used is PT Pos Indonesia. Atambua Branch Post Office is one of the branches of PT Pos Indonesia which operates for the Belu Regency area, East Nusa Tenggara Province. The formulation of the problems in this study are (1) How is the responsibility given by PT. Pos Indonesia Atambua Branch for the delivery of lost or damaged goods? (2) How are the obstacles to the implementation of the responsibility for lost or damaged goods provided by PT. Pos Indonesia Atambua Branch? The type of research used by the author is Empirical Legal research, the type of data used in this research is qualitative data. The data used in the research based on the relevance of the source data, namely primary and secondary data. The results of the study suggest that: (1) Liability for lost shipments by PT Pos Indonesia Atambua Branch, namely by providing compensation of 1 (one) x shipping costs and plus one time compensation guarantee that has been included in the proof of delivery receipt. If the shipment is damaged but part of the shipment can still be functioned, PT Pos Indonesia Atambua Branch provides compensation of 1 (one) x shipping costs and plus half x the cost of the guarantee of compensation that has been included in the proof of delivery receipt, but if it is totally damaged and loses its function, it will be given compensation of 1 (one) x shipping costs and add 1 (one) x the cost of compensation that has been included in the proof of delivery receipt. (2) The inhibiting factors are the lack of communication between PT Pos Indonesia and service users, negligence from PT Pos Indonesia Atambua Branch (Courier) which still often closes communication with the Foreman related to these problems.